2014
DOI: 10.1007/s00277-014-2204-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of dicentric chromosome (9;20) in paediatric B-cell acute lymphoblastic leukaemia: prognostic significance

Abstract: The dicentric chromosome (9;20) (dic(9;20)) is described in 2 % of childhood B-acute lymphoblastic leukaemia. Fluorescence in situ hybridization (FISH) is the most reliable method to identify dic(9;20) when compared with conventional cytogenetics. To define the prognostic importance of dic(9;20), we evaluated treatment response and patient survival. This was a retrospective study in three French university centres. Patients' clinical and laboratory characteristics and treatment response are described. Nine chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…FISH with specific probes is considered to be the method of choice for reliable detection of dic (9;20) in routine clinical setting [33]. Letouzey et al [34] analysed 9 childhood ALL patients to define the prognostic importance of dic(9;20). All of the patients had at least one adverse prognostic feature and the study concluded that dic(9;20) is associated with worse prognosis and that the patients should receive more intensive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…FISH with specific probes is considered to be the method of choice for reliable detection of dic (9;20) in routine clinical setting [33]. Letouzey et al [34] analysed 9 childhood ALL patients to define the prognostic importance of dic(9;20). All of the patients had at least one adverse prognostic feature and the study concluded that dic(9;20) is associated with worse prognosis and that the patients should receive more intensive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The current policies of TKI treatment of chronic phase CML mandate using TKIs at their respective approved or maximum tolerated doses lifelong, with the possibility of opening a window for treatment discontinuation when a DMR has been achieved and maintained for an as yet unspecified period of time. 3 , 5 , 12 , 16 , 40 The window for treatment discontinuation can be enlarged in some of the patients who received imatinib first line, by switching early or late to a second-generation TKI, 40 , 41 , 42 , 43 as well as using second-generation TKIs first line. 17 , 18 , 19 , 20 , 44 , 45 Other policies have not been tested prospectively, particularly for treatments alternative to discontinuation, when discontinuation is not possible.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 , 11 , 12 About 50% of them were reported to maintain that remission status after discontinuation of imatinib and to achieve a stable treatment-free remission (TFR). 13 , 14 , 15 , 16 The introduction of the so-called second-generation TKIs, both in first and second line, is expected to fare even better, with up to 50% or more of the patients achieving a DMR, 17 , 18 , 19 , 20 and up to ⩾50% of them entering into a TFR status. If these expectations will be fulfilled, the proportion of patients who will be in TFR will range between 25% and 50%.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that it is feasibly to improve the radiosensitivity for reducing the survival rate and increasing apoptosis by using drugs. Dicentric chromosome, as one of chromosome aberrations, is a chromosome containing two functional centromeres and considered to be the most accurate method for biological dosimetry in irradiation (16,26,27). It was reported that dicentric chromosome was frequently observed in cancer cells (28,29) and chromosomal rearrangements can radically alter gene products and their function, driving tumor formation or progression (30).…”
Section: Discussionmentioning
confidence: 99%
“…used to detect chromosome aberration in irradiated cells (16). In this study, dicentric chromosome ratio was determined in H1299 cells after irradiation with or without MG132.…”
Section: Mg132 Increased the Dicentric Chromosome Ratio Treated By Irmentioning
confidence: 99%